Two-dimensional vortex simulation of particulate airflow induced by free falling particles. (20th June 2008) - Uchiyama, Tomomi; Naruse, Masaaki
This paper is concerned with the numerical simulation for a particulate air flow induced by free falling solid particles. The particles are stationed within a rectangular region at the commencement of the fall. They are made to fall in an air, and the air flow induced by the falling particles as well as the particle motion is simulated. The simulation highlights that the falling particles induce large scale eddies and that the eddies convect with involving the particles when the particle volume fraction is high. It also reveals that the strength of large-scale eddy becomes lower with increasing the aspect ratio of the particle ensemble.